login

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 61st year, we have over 378,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”).

A186376
a(n) is the sum of the squares of the coefficients of (x + 2*y + 3*z)^n.
3
1, 14, 294, 7292, 198310, 5717124, 171485916, 5290989816, 166688596998, 5335746337460, 172951272017524, 5662840724506056, 186960502253087836, 6215612039963043368, 207865952390729881080, 6987002286567227550192
OFFSET
0,2
COMMENTS
a(n) equals the least sum of the squares of the coefficients in (1 + 2*x^k + 3*x^p)^n found at sufficiently large p for some fixed k>0.
Equivalently, a(n) equals the sum of the squares of the coefficients in any one of the following polynomials:
. (1 + 3*x^k + 2*x^p)^n, or
. (2 + x^k + 3*x^p)^n, or
. (3 + 2*x^k + x^p)^n, etc.,
for all p>(n+1)k and fixed k>0.
a(n) is the sum of the squares of the coefficients of (x + 2*y + 3*z)^n. - Michael Somos, Aug 25 2018
FORMULA
(1) a(n) = Sum_{k=0..n} C(n,k)^2 *Sum_{j=0..k} C(k,j)^2*4^(k-j)*9^j.
Let g.f. A(x) = Sum_{n>=0} a(n)*x^n/n!^2, then
(2) A(x) = B(x) * B(2^2*x) * B(3^2*x)
where B(x) = Sum_{n>=0} x^n/n!^2 = BesselI(0, 2*sqrt(x)).
Recurrence: n^2*(4*n - 7)*a(n) = 14*(16*n^3 - 44*n^2 + 34*n - 9)*a(n-1) - 196*(2*n - 3)^2*(4*n - 3)*a(n-2) + 144*(4*n - 9)*(4*n - 7)*(4*n - 3)*a(n-3). - Vaclav Kotesovec, Feb 12 2015
a(n) ~ 2^(2*n-1) * 3^(2*n+1) / (Pi*n). - Vaclav Kotesovec, Feb 12 2015
EXAMPLE
G.f.: A(x) = 1 + 14*x + 294*x^2/2!^2 + 7292*x^3/3!^2 +...
The g.f. may be expressed as:
[Sum_{n>=0}x^n/n!^2]*[Sum_{n>=0}(4x)^n/n!^2]*[Sum_{n>=0}(9x)^n/n!^2].
MATHEMATICA
Table[Sum[Binomial[n, k]^2 * Sum[Binomial[k, j]^2 * 4^(k-j) * 9^j, {j, 0, k}], {k, 0, n}], {n, 0, 20}] (* Vaclav Kotesovec, Feb 11 2015 *)
a[ n_] := If[ n < 0, 0, Block[ {x, y, z}, Expand[(x + y + 2 z)^n] /. {t_Integer -> t^2, x -> 1, y -> 2, z -> 3}]]; (* Michael Somos, Aug 25 2018 *)
PROG
(PARI) {a(n)=local(V=Vec((1+2*x+3*x^(n+2))^n)); V*V~}
(PARI) {a(n)=sum(k=0, n, binomial(n, k)^2*sum(j=0, k, binomial(k, j)^2*4^(k-j)*9^j))}
(PARI) {a(n)=n!^2*polcoeff(sum(m=0, n, x^m/m!^2)*sum(m=0, n, (2^2*x)^m/m!^2)*sum(m=0, n, (3^2*x)^m/m!^2), n)}
CROSSREFS
KEYWORD
nonn
AUTHOR
Paul D. Hanna, Feb 19 2011
EXTENSIONS
Name changed to match the definition given by Michael Somos. - Paul D. Hanna, Sep 05 2018
STATUS
approved